Improving the Body Area Line-of-Sight Density Model: A Theoretical Study - Xiaodong Yang; Zhiya Zhang; Shuyuan Yang; Qammer Hussain Abbasi; Wei Zhao (International Journal of Antennas and Propagation)
The statistical model plays an important role in BAN radio propagation characterization. However, a traditional least-square statistical model is not necessarily the best choice when only limited samples can be collected. This paper proposes the method for improving the density model in BAN radio propagation characterization; the final PDF result validates the correctness of the method.